Twenty-year-old female with leiomyosarcoma of the breast - Bassett, Parker (Oxford University Press, 2014)
Primary leiomyosarcoma is a disease with <50 documented cases in the literature worldwide. The standard of care for these tumors has not been established. Physicians who have seen these cases in the past have used wide local excision with or without adjunctive chemo-radiation therapy. We review the literature concerning the mainstay of treatment as well as present a new case of an adolescent with primary leiomyosarcoma.